2022
DOI: 10.1001/jamahealthforum.2022.4001
|View full text |Cite|
|
Sign up to set email alerts
|

Coverage and Prior Authorization Policies for Medications for Opioid Use Disorder in Medicaid Managed Care

Abstract: ImportanceMedicaid is a key policy lever to improve opioid use disorder treatment, covering approximately 40% of Americans with opioid use disorder. Although approximately 70% of Medicaid beneficiaries are enrolled in comprehensive managed care organization (MCO) plans, little is known about coverage and prior authorization (PA) policies for medications for opioid use disorder (MOUD) in these plans.ObjectiveTo compare coverage and PA policies for buprenorphine, methadone, and injectable naltrexone across Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Most Medicaid/CHIP agencies contract MCOs to administer benefits; nearly 70% of all Medicaid members across the USA are enrolled in MCOs [34]. MCOs can impose their own utilization management restrictions that differ from those of the state agency and are not evidence-based [16,35]. For example, some MCOs have denied MOUD for members who return to substance use [36].…”
Section: Policy Misalignment and Limited Access To Medications For Op...mentioning
confidence: 99%
See 1 more Smart Citation
“…Most Medicaid/CHIP agencies contract MCOs to administer benefits; nearly 70% of all Medicaid members across the USA are enrolled in MCOs [34]. MCOs can impose their own utilization management restrictions that differ from those of the state agency and are not evidence-based [16,35]. For example, some MCOs have denied MOUD for members who return to substance use [36].…”
Section: Policy Misalignment and Limited Access To Medications For Op...mentioning
confidence: 99%
“…For example, some MCOs have denied MOUD for members who return to substance use [36]. A recent national survey of Medicaid plan coverage found that nearly 36% of MCOs surveyed require prior authorization for MOUD, with MCOs differentially imposing these policies on access to buprenorphine, methadone, and naltrexone [35].…”
Section: Policy Misalignment and Limited Access To Medications For Op...mentioning
confidence: 99%
“…In 2019, New Jersey Medicaid implemented the MATrx model, which included initiatives designed to reduce barriers to buprenorphine prescribing in the Medicaid program and support clinicians in establishing or expanding capacity to deliver office-based addiction treatment. Under this model, Medicaid prohibited managed care organizations from requiring prior authorizations for MOUDs, to which most New Jersey Medicaid enrollees were subject before 2019 . Medicaid also implemented the Office Based Addiction Treatment (OBAT) program, enhancing reimbursement for office-based MOUD visits in clinics offering patient navigation .…”
Section: Introductionmentioning
confidence: 99%
“…Under this model, Medicaid prohibited managed care organizations from requiring prior authorizations for MOUDs, 18 to which most New Jersey Medicaid enrollees were subject before 2019. 19 Medicaid also implemented the Office Based Addiction Treatment (OBAT) program, enhancing reimbursement for office-based MOUD visits in clinics offering patient navigation. 18 The program further created new reimbursement codes for patient navigation in OBATs, which could be provided by nurses, social workers, medical assistants, or others who meet training and experiential requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In the Original Investigation titled “Coverage and Prior Authorization Policies for Medications for Opioid Use Disorder in Medicaid Managed Care,” published November 4, 2022, the titles for Figures 3 and 5 have been corrected to include mention of fee-for-service programs; the titles had originally only mentioned managed care organization plans, when these figures in fact report on both. This article has been corrected …”
mentioning
confidence: 99%